Rubber composition for transmission belt, transmission belt, and method for producing transmission belt

By using the combination of specific proportions of clothe rubber, Fang Polyamine short fiber, adhesive improvement and charcoal black in the compressed rubber layer, solve the difficulty of improving wear resistance, saving fuel, and saving fuel, saving fuel, and saving fuel. The problem of turtle resistance has achieved efficient performance improvement and is suitable for gear transmission in high -horsepower machinery.

CN119365702APending Publication Date: 2025-01-24MITSUBOSHI BELTING LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380050158.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-30
Filing Date
2023-06-20
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to improve wear resistance, fuel saving and crack resistance in the transmission belt at the same time, especially in gearboxes used in high-horsepower machinery, and the prior art is difficult to meet the needs of these characteristics.

Method used

Compressed rubber layer formed by a compressed rubber layer formed by a specific proportional combination, short fiber that contains the short fiber of the ethyus polyamide, the adhesive improvement agent and the charcoal black, and improve the wear resistance, fuel nature and turtle resistance of the transmission belt Cracking.

Benefits of technology

The abrasion resistance, provincial fuelability and turtle resistance of the transmission belt are realized at the same time, ensuring high productivity rubber composition preparation, and suitable for gear transmission in high -horsepower machinery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365702A_ABST
    Figure CN119365702A_ABST
Patent Text Reader

Abstract

The present invention relates to a rubber composition for use in a compressed rubber layer of a transmission belt, the rubber composition comprising chloroprene rubber, short fibers, an adhesion improving agent, and carbon black, the short fibers comprising aramid short fibers, the ratio of the short fibers being 15-38 parts by mass per 100 parts by mass of the chloroprene rubber, and the ratio of the short fibers to the carbon black being 15-38 parts by mass per 100 parts by mass of the chloroprene rubber. The proportion of the aramid short fibers is 5-28 parts by mass, the proportion of the adhesion improving agent is 0.1-3.2 parts by mass, and the proportion of the carbon black is 30-70 parts by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rubber composition capable of forming a compression rubber layer of a transmission belt such as a speed change belt, a transmission belt including a compression rubber layer formed of the rubber composition, and a method for producing the same. Background Art

[0002] The transmission belts used in the power transmission mechanism of mechanical devices are roughly divided into friction transmission belts and meshing transmission belts according to the power transmission method. As friction transmission belts, V-belts, multi-V belts, flat belts, etc. are known, and as meshing transmission belts, toothed belts are known.

[0003] As an example of V-belts, there are trimmed-edge type belts (trimmed-edge V-belts) whose friction transmission surface (V-shaped side surface) is an exposed rubber layer. Among trimmed-edge type belts, in addition to trimmed-edge V-belts without cogs, there are trimmed-edge toothed V-belts with cogs only on the inner circumference of the belt to improve the bending property, and trimmed-edge toothed V-belts with cogs on both the inner circumference and outer circumference of the belt to improve the bending property (trimmed-edge double-sided toothed V-belts).

[0004] As the use of these V-belts (especially cut-edge toothed V-belts), belt-type continuously variable transmissions can be cited. Figure 1A and Figure 1B As shown, the belt-type continuously variable transmission 30 is a device that winds a V-belt 1 on a driving pulley 31 and a driven pulley 32 to change the speed ratio infinitely. Each pulley 31, 32 has a fixed pulley 31a or 32a whose axial movement is restricted or fixed, and a movable pulley 31b or 32b that can move in the axial direction. Each pulley 31, 32 has a structure that can continuously change the width of the V-groove formed by these fixed pulleys 31a or 32a and the movable pulley 31b or 32b. The two end surfaces in the width direction of the above-mentioned V-belt 1 have conical surfaces that are inclined in the same manner as the opposite surfaces of the V-groove of each pulley 31, 32, and are embedded in any position in the radial direction of the pulley according to the width of the changed V-groove. For example, if the width of the V-groove of the driving pulley 31 is narrowed and the width of the V-groove of the driven pulley 32 is widened, Figure 1A The status shown changes to Figure 1B In the state shown, the V-belt 1 moves toward the outer circumference of the pulley radius on the driving pulley 31 side and moves toward the inner circumference of the pulley radius on the driven pulley 32 side. Thus, the winding radius on each pulley 31, 32 changes continuously, and the speed ratio can be infinitely changed.

[0005] The V-belt (variable speed belt) used in such applications is specially designed to withstand not only the winding and rotating movement between the two axes of the driving pulley and the driven pulley, but also the movement in the radial direction of the pulley and the repeated bending caused by the continuous change of the winding radius.

[0006] For example, Japanese Patent Application Laid-Open No. 2004-3609 (Patent Document 1) discloses a transmission belt in which a rubber compound forming a compression rubber layer comprises 100 parts by mass of chloroprene rubber, 1 to 40 parts by mass of polyparaphenylene benzodiazole, and 100 parts by mass of chloroprene rubber. The invention discloses a vulcanized rubber having a short fiber, 10 to 60 parts by weight of carbon black, and 0.5 to 10 parts by weight of N-N'-m-phenylene bismaleimide as a vulcanization accelerator. It is also described that when the content of N-N'-m-phenylene bismaleimide is less than 0.5 parts by weight, the crosslinking density becomes small and the effect of improving the wear resistance is small. When the content exceeds 10 parts by weight, the elongation of the vulcanized rubber decreases significantly and the bending resistance decreases.

[0007] Japanese Patent Application Publication No. 2012-241831 (Patent Document 2) discloses a transmission belt, wherein the compression rubber layer contains fatty acid amide and short fibers. It is also recorded that the fatty acid amide improves the dispersibility and orientation of the short fibers, improves the adhesion between the rubber component and the short fibers, and precipitates on the surface of the compression rubber layer, thereby reducing the friction coefficient of the rubber layer surface and improving the transmission efficiency.

[0008] Japanese Patent Publication No. 2014-209026 (Patent Document 3) discloses a transmission belt, wherein the compression rubber layer contains chloroprene rubber, short fibers, and polyolefin resin. It is also recorded that, in general, in order to improve fuel efficiency, short fibers are excessively added to reduce the friction coefficient, but cracks are easily generated at the interface between the rubber component and the short fibers, and durability may be impaired. If a polyolefin resin is added, the friction coefficient of the compression rubber layer can be reduced and the wear resistance of the belt can be improved.

[0009] As disclosed in these documents, it is a known technology to reduce the friction coefficient and improve the wear resistance and fuel efficiency by adding short fibers to the compression rubber layer of the V-belt. Patent documents 1 to 3 are characterized by combining short fibers with N-N'-m-phenylene bismaleimide, fatty acid amide, polyolefin resin, etc., and as another method, attempts have also been made to improve the type of short fibers.

[0010] For example, Japanese Patent Application Laid-Open No. 4-366045 (Patent Document 4) discloses a transmission belt in which a portion of aramid short fibers are replaced with nylon fibers, and states that the elastic modulus is mainly increased by the aramid fibers, while the friction coefficient is stabilized by the nylon fibers.

[0011] Japanese Patent Publication No. 2010-151209 (Patent Document 5) discloses a transmission belt, in which the friction coefficient is within a specific range by adding short fibers and a lubricant to the compression rubber layer. It is also recorded that the short fibers can be meta-aramid fibers that have not been fibrillated. It is also recorded that in the prior art, short fibers such as para-aramid fibers are used for fibrillation. In contrast, by using short fibers such as meta-aramid short fibers that have not been fibrillated, a specified friction coefficient can be obtained with a small amount of addition compared to the case of using short fibers that have been fibrillated.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Publication No. 2004-3609

[0015] Patent Document 2: Japanese Patent Application Publication No. 2012-241831

[0016] Patent Document 3: Japanese Patent Application Publication No. 2014-209026

[0017] Patent Document 4: Japanese Patent Application Laid-Open No. 4-366045

[0018] Patent Document 5: Japanese Patent Application Publication No. 2010-151209 Summary of the invention

[0019] Problems to be solved by the invention

[0020] However, when adding short fibers to the compression rubber layer of a V-belt to reduce the friction coefficient as in Patent Documents 1 to 3, increasing the amount of short fibers tends to reduce crack resistance, making it difficult to simultaneously improve wear resistance, fuel economy, and crack resistance.

[0021] On the other hand, even the belts having the configurations disclosed in Patent Documents 4 and 5 show some effects on improving wear resistance, fuel efficiency, and crack resistance, but they still cannot be said to have fully achieved the required levels. In particular, in motorcycles, four-wheeled all-terrain vehicles, snowmobiles, and agricultural machinery represented by harvesters that use speed belts, the horsepower is being increased, and it is difficult to provide a rubber composition that fully satisfies these characteristics using the prior art.

[0022] Therefore, an object of the present invention is to provide a rubber composition capable of simultaneously improving wear resistance, fuel efficiency and crack resistance when used in a transmission belt, and a transmission belt capable of simultaneously improving wear resistance, fuel efficiency and crack resistance.

[0023] Methods used to solve problems

[0024] The present inventors have discovered that in order to solve the above-mentioned problems, by combining chloroprene rubber, short fibers including aromatic polyamide short fibers, an adhesion improver and carbon black in a specific ratio to form a compression rubber layer of a transmission belt, the wear resistance, fuel economy and crack resistance of the transmission belt can be improved at the same time, thereby completing the present invention.

[0025] That is, the rubber composition according to the embodiment [1] of the present invention is a rubber composition for a compression rubber layer of a transmission belt, wherein:

[0026] The rubber composition comprises chloroprene rubber, short fibers, an adhesion improver and carbon black.

[0027] The short fibers include aramid short fibers,

[0028] Relative to 100 parts by mass of the chloroprene rubber, the proportion of the short fibers is 15 to 38 parts by mass, the proportion of the aromatic polyamide short fibers is 5 to 28 parts by mass, the proportion of the adhesion improver is 0.10 to 3.20 parts by mass, and the proportion of the carbon black is 30 to 70 parts by mass.

[0029] Aspect [2] of the present invention is the aspect described in aspect [1] above, wherein the short fibers further include aliphatic polyamide short fibers, and the ratio of the aliphatic polyamide short fibers to 100 parts by mass of the chloroprene rubber is 25 parts by mass or less.

[0030] Aspect [3] of the present invention is an aspect in which, in the aspect [2], the average fiber length of the aliphatic polyamide staple fibers is 1.5 mm or more.

[0031] Aspect [4] of the present invention is the aspect in which, in any one of aspects [1] to [3], the carbon black contains soft carbon.

[0032] Aspect [5] of the present invention is the aspect in which, in any one of aspects [1] to [4], the adhesion improver contains a phenol resin and / or an amino resin.

[0033] The present invention further includes, as aspect [6], a transmission belt including a compression rubber layer, wherein the compression rubber layer includes the rubber composition according to any one of aspects [1] to [5].

[0034] The present invention further includes, as embodiment [7], a method for producing a transmission belt, comprising a kneading step of kneading the rubber composition of any one of embodiments [1] to [5] to produce an uncrosslinked rubber sheet for forming a compression rubber layer.

[0035] Effects of the Invention

[0036] In the present invention, as a rubber composition for forming a compression rubber layer of a transmission belt, chloroprene rubber, short fibers including aramid short fibers, an adhesion improver and carbon black are combined in a specific ratio, so that the wear resistance, fuel saving and crack resistance of the transmission belt can be improved at the same time. In particular, unlike the conventional technical common sense, the workability is not reduced due to the tackiness of the adhesion improver, and the rubber composition can be prepared with high productivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1A It is a schematic diagram for explaining the speed change mechanism of a belt-type continuously variable transmission.

[0038] Figure 1B It is a schematic diagram for explaining the speed change mechanism of a belt-type continuously variable transmission.

[0039] Figure 2 This is a schematic cross-sectional perspective view showing an example of the power transmission belt of the present invention.

[0040] Figure 3 Yes Figure 2 A schematic cross-sectional view of a transmission belt cut along the length of the belt.

[0041] Figure 4 It is a schematic diagram for explaining the method of measuring bending stress in Examples.

[0042] Figure 5 The following is a layout of a transmission efficiency test of a cut-edge toothed V-belt obtained in an example.

[0043] Figure 6 The following is a layout of a wear endurance test of a cut-edge toothed V-belt obtained in an example.

[0044] Figure 7 The following is a layout of a crack durability test of a cut-edge toothed V-belt obtained in an example. DETAILED DESCRIPTION

[0045] The rubber composition of the present invention is characterized in that an adhesion improver is blended in the rubber composition for a compression rubber layer with a view to improving the adhesion between the rubber component and the short fibers.

[0046] It should be noted that in a transmission belt, it is a known technology to bury short fibers parallel to the width direction of the transmission belt to improve wear resistance while maintaining fuel economy. In order to take into account both wear resistance and fuel economy, there is a method of increasing the amount of short fibers without making the rubber itself too hard. However, if the amount of short fibers is increased, there is a tendency for crack resistance to decrease. It is believed that the reason for this tendency is that the adhesion between the rubber component and the short fibers is low. In this regard, in order to improve the adhesion between the rubber component and the short fibers, an adhesion improver is usually added to the bonding rubber, but sometimes adhesion is easily caused at the stage of mixing the rubber composition, which reduces the operability, and an adhesion improver is usually not added to the compression rubber layer.

[0047] In order to improve the wear resistance, there is also a method of increasing the hardness of the rubber itself by adding a large amount of reinforcing agents such as carbon black, crosslinking agents, crosslinking accelerators, co-crosslinking agents, etc., but the flexibility is reduced and the fuel saving performance is reduced.

[0048] In contrast, the basic design concept of the present invention is to improve wear resistance and fuel efficiency by using short fibers while maintaining crack resistance by combining with an adhesion improver.

[0049] [Neoprene]

[0050] The rubber composition of the present invention contains chloroprene rubber as an essential rubber component from the viewpoint of good balance of wear resistance, heat resistance, cold resistance, weather resistance, etc. and excellent adhesion to short fibers. The chloroprene rubber may be sulfur-modified or non-sulfur-modified.

[0051] In the rubber composition of the present invention, the rubber component may include other rubbers in addition to chloroprene rubber. As other rubber components, diene rubbers other than chloroprene rubber [natural rubber, isoprene rubber, butadiene rubber, styrene butadiene rubber (SBR), acrylonitrile butadiene rubber (nitrile rubber), hydrogenated nitrile rubber (including a mixed polymer of hydrogenated nitrile rubber and an unsaturated carboxylic acid metal salt), etc.], ethylene-α-olefin elastomers, chlorosulfonated polyethylene rubber, alkylated chlorosulfonated polyethylene rubber, epichlorohydrin rubber, acrylic rubber, silicone rubber, polyurethane rubber, fluororubber, etc. can be listed.

[0052] The ratio of other rubber components to 100 parts by mass of the chloroprene rubber may be 100 parts by mass or less, preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 10 parts by mass or less.

[0053] The proportion of chloroprene rubber in the rubber component can be 50% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and most preferably 100% by mass (i.e., chloroprene rubber is used alone). In addition, the proportion of chloroprene rubber in the rubber composition of the present invention can be 30% by mass or more, preferably 30 to 70% by mass, more preferably 40 to 60% by mass, more preferably 42 to 52% by mass, and most preferably 44 to 48% by mass.

[0054] [Short Fiber]

[0055] In order to improve the wear resistance of the compression rubber layer and reduce the friction coefficient, the rubber composition of the present invention contains short fibers as an essential component. In particular, if the short fibers are oriented in the belt width direction and embedded in the compression rubber layer, the compression deformation of the transmission belt due to the pressure from the pulley can be suppressed, so that the wear resistance can be improved while maintaining fuel saving. As a method for orienting the short fibers in the belt width direction, for example, a method of calendering using a roller can be cited.

[0056] (aramid staple fiber)

[0057] In order to improve the wear resistance of the power transmission belt, the short fibers contain aramid short fibers as essential fibers.

[0058] The aramid fibers constituting the aramid staple fibers may be para-aramid fibers or meta-aramid fibers.

[0059] Examples of the para-aramid fiber include poly(p-phenylene terephthalamide) fibers (e.g., “TOWARON (registered trademark)” manufactured by Teijin Limited, “KEBLA (registered trademark)” manufactured by DuPont Toray Industries, etc.), and copolymer fibers of poly(p-phenylene terephthalamide) and 3,4′-oxydiphenylene terephthalamide (e.g., “TEKNOLA (registered trademark)” manufactured by Teijin Limited, etc.).

[0060] Examples of the meta-aramid fiber include polymetaphenylene isophthalamide fiber (for example, “CONEX (registered trademark)” manufactured by Teijin Limited, etc.).

[0061] These aromatic polyamide fibers can be used alone or in combination of two or more. Among them, meta-aramid fibers are preferred from the perspective of having a large effect of reducing the friction coefficient of the compression rubber layer and being able to improve fuel economy. In particular, when only aromatic polyamide staple fibers are used as staple fibers, meta-aramid fibers are preferred from the perspective of being able to improve transmission efficiency and being able to improve fuel economy. When aromatic polyamide staple fibers are combined with other staple fibers, bending fatigue resistance and crack resistance can be improved, and from the perspective of being well balanced with fuel economy, para-aramid staple fibers are preferred as aromatic polyamide staple fibers, and a combination of para-aramid staple fibers and aliphatic polyamide staple fibers described later is particularly preferred.

[0062] The average fiber diameter of the aramid short fibers is, for example, 2 μm or more, preferably 2 to 100 μm, more preferably 3 to 50 μm, more preferably 7 to 40 μm, and most preferably 10 to 30 μm. If the average fiber diameter of the aramid short fibers is too small, the friction coefficient of the surface of the compression rubber layer may not be sufficiently reduced.

[0063] The average fiber length of the aramid staple fibers is, for example, 1 to 20 mm, preferably 1.3 to 15 mm, more preferably 1.5 to 10 mm, more preferably 2 to 5 mm, and most preferably 2.5 to 4 mm. When the average fiber length of the aramid staple fibers is too short, the mechanical properties (such as modulus, etc.) in the grain direction may not be sufficiently improved, and the bending fatigue resistance and crack resistance may be reduced. On the contrary, when the average fiber length of the aramid staple fibers is too long, the aramid staple fibers in the rubber composition may be poorly dispersed, the friction coefficient of the surface may not be sufficiently reduced, and the transfer efficiency may be reduced.

[0064] It should be noted that in the present application, the average fiber diameter and the average fiber length of the aromatic polyamide staple fibers can be calculated, for example, by performing image analysis on photographs of the aromatic polyamide staple fibers taken with an electron microscope such as a transmission electron microscope and a scanning electron microscope in the form of the arithmetic average of the fiber diameter and the fiber length of an appropriate number of samples (e.g., 50 samples).

[0065] In order to suppress the compression deformation of the belt due to the pressure from the pulley, the aramid short fibers may be oriented substantially parallel to the belt width direction and embedded in the compression rubber layer.

[0066] It should be noted that, in the present application, "substantially parallel" to the belt width direction means an angle relative to the belt width direction of, for example, within 10°, preferably within 8°, further preferably within 5°, more preferably within 3°, and most preferably within 1° (for example, 0 to 1°, especially approximately 0°).

[0067] From the viewpoint of dispersibility and adhesiveness of the aramid short fibers in the rubber composition, the aramid short fibers may be subjected to an adhesive treatment or a surface treatment.

[0068] In the bonding treatment of the aramid staple fibers, various bonding treatment liquids can be used, such as a treatment liquid containing an initial condensate of phenols and formalin (a prepolymer of a linear or resol type phenolic resin, etc.), a treatment liquid containing a rubber component or latex, a treatment liquid containing the above initial condensate and a rubber component (latex), a treatment liquid containing a silane coupling agent, an epoxy compound (epoxy resin, etc.), an isocyanate compound, and other reactive compounds (adhesive compounds), etc. In a preferred bonding treatment, the aramid staple fibers are treated with a treatment liquid containing the above initial condensate and a rubber component (latex), in particular, at least a resorcinol-formalin-latex (RFL) liquid. Such treatment liquids can be used in combination, for example, the aramid staple fibers can be treated with a conventional adhesive component, such as an epoxy compound (epoxy resin, etc.), an isocyanate compound, and other reactive compounds (adhesive compounds), and then treated with an RFL liquid.

[0069] It should be noted that in the present application, among the short fibers (including other short fibers) mixed in the rubber composition, the adhesive compound that has been previously treated to bond the surface of the short fibers is not included in the scope of the adhesiveness improver mixed in the rubber composition described later. Therefore, the mass of the adhesive compound that has been previously treated to bond the surface of the short fibers is regarded as the mass of the short fibers (the mass of a part of the short fibers).

[0070] If such a treatment liquid, especially RFL liquid, is used for treatment, the aromatic polyamide staple fibers and chloroprene rubber can be strongly bonded. RFL liquid is a mixture of an initial condensate of resorcinol and formaldehyde and latex. The molar ratio of resorcinol to formaldehyde can be any range that can improve the adhesion between the rubber component and the staple fibers, and the former / the latter is, for example, 1 / 0.3 to 1 / 3, preferably 1 / 0.4 to 1 / 2, more preferably 1 / 0.5 to 1 / 1.5, more preferably 1 / 0.6 to 1 / 1, and most preferably 1 / 0.6 to 1 / 0.8.

[0071] The type of latex is not particularly limited, but diene rubber (styrene-butadiene-vinylpyridine terpolymer, chloroprene rubber, butadiene rubber, etc.) and chlorosulfonated polyethylene rubber are preferred, and styrene-butadiene-vinylpyridine terpolymer is particularly preferred.

[0072] The ratio of the initial condensate of resorcinol and formalin to 100 parts by mass of the rubber component of the latex is, for example, 10 to 100 parts by mass, preferably 12 to 50 parts by mass, and more preferably 15 to 30 parts by mass. It should be noted that the total solid content concentration of the RFL liquid can be adjusted within the range of 5 to 40% by mass.

[0073] The adhesion rate of the adhesive component (solid content) to the aromatic polyamide staple fibers [{(mass of the aromatic polyamide staple fibers after the adhesive treatment - mass of the aromatic polyamide staple fibers before the adhesive treatment) / (mass of the aromatic polyamide staple fibers after the adhesive treatment)}×100] is, for example, 1 to 25% by mass, preferably 2 to 20% by mass, further preferably 2.5 to 15% by mass, more preferably 3 to 10% by mass, and most preferably 4 to 8% by mass. When the adhesion rate of the adhesive component is too low, the dispersibility of the aromatic polyamide staple fibers in the rubber composition and the adhesion between the aromatic polyamide staple fibers and the rubber composition are insufficient. On the contrary, when the adhesion rate of the adhesive component is too high, the adhesive component may firmly fix the aromatic polyamide staple fibers to each other, and the dispersibility may be reduced.

[0074] The ratio of the aramid short fibers to 100 parts by mass of the chloroprene rubber is, for example, 5 to 28 parts by mass, preferably 10 to 25 parts by mass, more preferably 12 to 20 parts by mass, and more preferably 13 to 18 parts by mass. When the ratio of the aramid short fibers is too small, the wear resistance may be reduced. On the contrary, when the ratio of the aramid short fibers is too large, the effect of reducing the friction coefficient may be small, and the transmission efficiency may be reduced.

[0075] (Aliphatic polyamide staple fiber)

[0076] The short fibers may further include aliphatic polyamide short fibers (nylon short fibers). In order to improve wear resistance, aromatic polyamide short fibers are effective as essential fibers, but from the perspective of highly balancing wear resistance and fuel efficiency, it is preferably combined with aliphatic polyamide short fibers. On the other hand, when high wear resistance is required, only aromatic polyamide short fibers may be used as the short fibers.

[0077] Examples of the aliphatic polyamide fibers constituting the aliphatic polyamide staple fibers include polyamide 46 fibers, polyamide 6 fibers, polyamide 66 fibers, polyamide 610 fibers, polyamide 612 fibers, polyamide 11 fibers, and polyamide 12 fibers.

[0078] These aliphatic polyamide fibers can be used alone or in combination of two or more. Among them, polyamide 6 fiber, polyamide 66 fiber, etc. having C 4-8 Nylon fibers with alkylene chains.

[0079] The average fiber diameter of the aliphatic polyamide short fibers is, for example, 2 μm or more, preferably 2 to 100 μm, more preferably 3 to 50 μm, more preferably 7 to 40 μm, and most preferably 10 to 30 μm. If the average fiber diameter of the aliphatic polyamide short fibers is too small, the friction coefficient of the surface of the compression rubber layer may not be sufficiently reduced.

[0080] The average fiber length of the aliphatic polyamide staple fibers can be greater than 1 mm (for example, 1 to 20 mm). From the perspective of improving bending fatigue resistance and crack resistance, it is preferably greater than 1.5 mm (especially greater than 2 mm), further preferably 1.5 to 10 mm, more preferably 2 to 5 mm, and most preferably 2.5 to 4 mm.

[0081] It should be noted that in the present application, the average fiber diameter and the average fiber length of aliphatic polyamide staple fibers can be calculated, for example, by performing image analysis on photographs of aliphatic polyamide staple fibers taken with an electron microscope such as a transmission electron microscope and a scanning electron microscope in the form of the arithmetic average of the fiber diameter and fiber length of an appropriate number of samples (e.g., 50 samples).

[0082] In order to suppress the compressive deformation of the belt due to the pressure from the pulley, the aliphatic polyamide short fibers may be oriented substantially parallel to the belt width direction and embedded in the compression rubber layer.

[0083] From the viewpoint of dispersibility and adhesion of the aliphatic polyamide short fibers in the rubber composition, the aliphatic polyamide short fibers may be subjected to an adhesive treatment or a surface treatment. As the adhesive treatment, including preferred embodiments, it can be selected from the adhesive treatments exemplified as the adhesive treatments for the aromatic polyamide short fibers. The adhesive treatment for the aliphatic polyamide short fibers may be different from the adhesive treatment for the aromatic polyamide short fibers, but from the viewpoint of simplicity, the same adhesive treatment is preferably used.

[0084] The proportion of aliphatic polyamide staple fibers relative to 100 parts by mass of chloroprene rubber may be 25 parts by mass or less (e.g., 0 to 25 parts by mass), preferably 5 to 25 parts by mass, more preferably 10 to 20 parts by mass, and more preferably 12 to 18 parts by mass. The proportion of aliphatic polyamide staple fibers relative to 100 parts by mass of aromatic polyamide staple fibers may be 1000 parts by mass or less, preferably 600 parts by mass or less, more preferably 300 parts by mass or less, for example, 5 to 600 parts by mass (e.g., 20 to 500 parts by mass), preferably 10 to 200 parts by mass (e.g., 20 to 100 parts by mass), more preferably 30 to 100 parts by mass, more preferably 50 to 80 parts by mass, and most preferably 60 to 70 parts by mass. When the proportion of aliphatic polyamide staple fibers is too small, fuel saving and crack resistance may be reduced. When the proportion of aliphatic polyamide staple fibers is too large, wear resistance and crack resistance may be reduced.

[0085] (Ratio of other short fibers to total short fibers)

[0086] The short fibers may further include other short fibers other than aramid short fibers and nylon short fibers. Examples of other short fibers include polyolefin short fibers (polyethylene short fibers, polypropylene short fibers, etc.), polyalkylene arylate short fibers (polyethylene terephthalate (PET) short fibers, polyethylene naphthalate (PEN) short fibers, etc.), and polyolefin short fibers. 2-4 Alkylene C 6-14 Aromatic ester staple fibers, etc.], vinylon staple fibers, polyvinyl alcohol staple fibers, polyparaphenylene benzodione Synthetic short fibers such as polybutylene oxadiazole (PBO) short fibers; natural short fibers such as cotton, linen, wool, etc.; inorganic short fibers such as carbon short fibers, etc. These other short fibers can be used alone or in combination of two or more.

[0087] The proportion of other short fibers may be 50 parts by mass or less, preferably 30 parts by mass or less, and more preferably 10 parts by mass or less relative to 100 parts by mass of the aramid short fibers. The short fibers may substantially contain no other short fibers. That is, the short fibers may be short fibers consisting only of aramid short fibers, or may be short fibers consisting only of aramid short fibers and aliphatic polyamide short fibers.

[0088] The ratio of the short fibers (the ratio of the total amount of the short fibers) relative to 100 parts by mass of the chloroprene rubber is 15 to 38 parts by mass, preferably 20 to 35 parts by mass, and more preferably 20 to 30 parts by mass. When the ratio of the total amount of the short fibers is too small, the wear resistance may be reduced, and the friction coefficient cannot be sufficiently reduced, so the fuel saving performance is not improved. On the other hand, when the ratio of the total amount of the short fibers is too large, the crack resistance may be reduced.

[0089] [Adhesion Improver]

[0090] The rubber composition of the present invention contains an adhesion improver. In the rubber composition of the present invention, by mixing the adhesion improver with the chloroprene rubber and the short fibers, the wear resistance and fuel saving performance can be improved, and the crack resistance can be improved. In particular, by adjusting the ratio of the short fibers and the adhesion improver, the rubber composition can be prepared with high productivity.

[0091] As the adhesion improver, the conventional adhesion improver utilized as the adhesion improver of the adhesive rubber layer can be utilized. As the conventional adhesion improver, for example, phenolic resin, amino resin, epoxy compound, isocyanate compound etc. can be cited. These adhesion improvers can be used alone or in combination of two or more. Among them, from the aspect that can improve the crack resistance, preferably phenolic resin and / or amino resin.

[0092] It should be noted that, in the present application, “A and / or B” means “at least one of A and B”.

[0093] (Phenolic resin)

[0094] The phenolic resin (phenolic resin) may be a co-condensate containing a unit in which aldehydes are condensed with phenols.

[0095] Examples of phenols include aromatic monohydric alcohols such as phenol and alkylphenols (such as cresol, etc.); aromatic polyhydric alcohols such as catechol, resorcin, hydroquinone, pyrogallol, etc.; aminophenols such as 3-aminophenol and 4-aminophenol, etc. These phenols may be used alone or in combination of two or more.

[0096] Among these phenols, aromatic monohydric alcohols such as phenol and cresol and aromatic polyhydric alcohols such as resorcinol are preferred, and at least one selected from the group consisting of phenol, cresol and resorcinol is particularly preferred.

[0097] In addition to phenols, the phenolic resin may also contain a compound having an amino group (amino-containing compound) as a compound condensed with formaldehyde. As the amino-containing compound, for example, melamine, urea, guanamine (formylguanamine, acetylguanamine, benzoguanamine, etc.), aniline, etc. can be cited. These compounds can be used alone or in combination of two or more. Among them, amino-containing cyclic compounds such as melamine are preferred.

[0098] The ratio of the amino group-containing compound to 100 parts by mass of phenols may be 100 parts by mass or less (eg, 1 to 100 parts by mass), preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 10 parts by mass or less.

[0099] Examples of the aldehydes include aliphatic aldehydes such as formaldehyde, acetaldehyde, and propionaldehyde; aromatic aldehydes such as phenylacetaldehyde; and condensates of formaldehyde such as trioxymethylene and paraformaldehyde.

[0100] These aldehydes can be used alone or in combination of two or more. Of these aldehydes, formaldehyde and paraformaldehyde are preferred, and formaldehyde is particularly preferred. Formaldehyde is usually used in the form of formalin.

[0101] The ratio of the total amount of phenols and amino group-containing compounds to aldehydes is (molar ratio) 1 / 0.5 to 1 / 5, for example, preferably 1 / 0.6 to 1 / 4, and more preferably 1 / 0.7 to 1 / 3.

[0102] The phenolic resin may be, for example, a reaction product (e.g., an initial condensate or a prepolymer) obtained by reacting a phenol containing resorcinol with an aldehyde in the presence of water and an alkali catalyst (alkali metal salts such as sodium hydroxide; alkaline earth metal salts; ammonia, etc.). The phenolic resin is preferably a phenol-formaldehyde co-condensate, a cresol-formaldehyde co-condensate, a resorcinol-formaldehyde co-condensate, a resorcinol-phenol-formaldehyde co-condensate, a resorcinol-cresol-formaldehyde co-condensate, and a resorcinol-melamine-formaldehyde co-condensate, and particularly preferably a phenol-formaldehyde co-condensate, a cresol-formaldehyde co-condensate, and a resorcinol-formaldehyde co-condensate. The phenol-formaldehyde co-condensate may be a linear phenolic resin.

[0103] (Amino resin)

[0104] The amino resin may be a co-condensate of an amino group-containing compound and an aldehyde. The amino resin may also be a reaction product (eg, an initial condensate or a prepolymer) obtained by reacting an amino group-containing compound with an aldehyde under neutral or alkaline conditions.

[0105] Examples of the amino group-containing compound include melamine, urea, guanamine (formylguanamine, acetoguanamine, benzoguanamine, etc.), and aniline.

[0106] Examples of the aldehydes include the aldehydes exemplified in the section of the phenol resin, etc. Among the aldehydes described above, formaldehyde is preferred.

[0107] As a ratio of the amino group-containing compound to the aldehyde, the former / the latter (molar ratio) is, for example, 1 / 1 to 1 / 10, preferably 1 / 3 to 1 / 8, and more preferably 1 / 5 to 1 / 7.

[0108] The amino resin may be a conventional amino resin such as melamine resin, urea resin (urea resin), guanamine resin, aniline resin, etc. Among them, melamine resin, urea resin (hydroxymethyl urea, etc.), guanamine resin (hydroxymethyl benzoguanamine, etc.) are preferred, and melamine resin is particularly preferred.

[0109] As the melamine resin, for example, general-purpose trimethylol melamine, monomethylol melamine to hexamethylol melamine such as hexamethylol melamine, etc., preferably tetramethylol melamine to hexamethylol melamine (especially hexamethylol melamine). From the perspective of operability, etc., the melamine resin (especially tetramethylol melamine to hexamethylol melamine) can be made of an alkyl group (for example, methyl, ethyl, n-butyl, isobutyl, etc.) 1-4 As the etherified alkyl ether melamine resin, for example, the general mono C 1-4 Alkoxymethyl melamine~hexa-C 1-4 Alkoxymethyl melamine, etc., preferably hexamethoxymethyl melamine, hexa-n-butoxymethyl melamine, hexaisobutoxymethyl melamine, etc. 1-4 Alkoxymethyl melamine. In addition, the melamine resin may be a compound containing other amino groups together with melamine, such as urea, guanamine (formylguanamine, acetoguanamine, benzoguanamine, etc.), aniline, etc. The ratio of other amino group-containing compounds to 1 mol of melamine may be 0.3 mol or less (particularly 0.1 mol or less).

[0110] (Proportion of Adhesion Improver)

[0111] Relative to 100 parts by mass of chloroprene rubber, the ratio of the adhesion improver (first adhesion improver) in the rubber composition of the present invention can be selected from the range of about 0.10 parts by mass to about 3.20 parts by mass, for example, 0.2 to 3.1 parts by mass, preferably 0.25 to 3 parts by mass, further preferably 0.3 to 2.5 parts by mass, more preferably 0.5 to 2 parts by mass, and most preferably 0.8 to 1.5 parts by mass. When the ratio of the adhesion improver is too small, crack resistance may be reduced. On the contrary, when the ratio of the adhesion improver is too large, adhesion may occur in the mixing process (mixing process), and productivity may be reduced.

[0112] [Carbon black]

[0113] In order to improve wear resistance, the rubber composition of the present invention further comprises a predetermined amount of carbon black. In the present invention, wear resistance can be improved by combining the above-mentioned short fibers with the above-mentioned adhesion improver, so that wear resistance can be improved without adding a large amount of carbon black. Therefore, bendability can also be improved.

[0114] Carbon black is generally classified into several grades based on differences in average primary particle size, iodine adsorption, nitrogen adsorption specific surface area, etc. Regarding the classification of carbon black, in ASTM, it is classified into N0 based on iodine adsorption. ~N9 However, the previous classification (SAF, HAF, GPF, etc.) based on the performance of the rubber product after compounding is also used. Sometimes N110 (SAF), N220 (ISAF), N330 (HAF), etc. with a small average primary particle size are also called hard carbon, and N550 (FEF), N660 (GPF), N762 (SRF), etc. with a large average primary particle size are also called soft carbon. The iodine adsorption amount is closely related to the average primary particle size. The smaller the average primary particle size, the greater the iodine adsorption amount. Taking the シースト (registered trademark) series manufactured by Tokai Carbon Co., Ltd. as an example to classify carbon black, if the iodine adsorption amount and the average primary particle size are summarized, the relationship becomes as shown in Table 1.

[0115] [Table 1]

[0116]

[0117] In the present application, the carbon black contained in the rubber composition is not classified according to the raw materials, but the carbon black with an average primary particle size of 40nm or more is called soft carbon, and the carbon black with an average primary particle size of less than 40nm is called hard carbon.

[0118] In addition, in this application, the average primary particle size of carbon black can be measured using, for example, a transmission electron microscope or the like.

[0119] The average primary particle size of the soft carbon may be 40 nm or more, and the maximum primary particle size of the soft carbon may be, for example, 300 nm or less, preferably 200 nm or less, and more preferably 100 nm or less. If the maximum primary particle size of the soft carbon is too large, the wear resistance may not be improved.

[0120] The average primary particle size of the soft carbon is, for example, 40 to 100 nm, preferably 41 to 80 nm, more preferably 42 to 60 nm, and more preferably 43 to 50 nm. If the average primary particle size of the soft carbon is too small, fuel saving may be reduced. On the contrary, if the average primary particle size of the soft carbon is too large, the effect of improving wear resistance may not be shown.

[0121] The iodine adsorption of the soft carbon may be less than 60 g / kg, for example, 10 g / kg or more and less than 60 g / kg, preferably 20 to 58 g / kg, more preferably 30 to 55 g / kg, and even more preferably 40 to 50 g / kg. If the iodine adsorption is too high, fuel saving may be reduced.

[0122] It should be noted that, in the present application, the iodine adsorption of carbon black can be measured according to the standard test method of ASTM D1510-17.

[0123] The average primary particle size of the hard carbon may be less than 40 nm, and the maximum primary particle size of the hard carbon may be, for example, 38 nm or less, preferably 35 nm or less, and more preferably 30 nm or less.

[0124] The average primary particle size of the hard carbon is, for example, 10 to 35 nm, preferably 12 to 33 nm, more preferably 15 to 30 nm, and further preferably 20 to 25 nm.

[0125] The iodine adsorption amount of the hard carbon may be 60 g / kg or more, for example, 60 to 150 g / kg, preferably 80 to 130 g / kg, more preferably 100 to 130 g / kg, and even more preferably 120 to 125 g / kg.

[0126] In the present invention, from the aspect of reducing the friction coefficient and the internal heat generation when the belt is bent to improve the fuel saving performance, the carbon black preferably contains soft carbon. The proportion of soft carbon in the carbon black can be 10% by mass or more, preferably 50% by mass or more, more preferably 80% by mass or more, more preferably 90% by mass or more, and most preferably 100% by mass.

[0127] The ratio of carbon black (first carbon black) in the rubber composition of the present invention is 30 to 70 parts by mass, preferably 35 to 65 parts by mass, more preferably 40 to 60 parts by mass, and more preferably 45 to 55 parts by mass, relative to 100 parts by mass of chloroprene rubber. When the ratio of carbon black is too small, the bending stress and wear resistance of the belt may be reduced. On the other hand, when the ratio of carbon black is too large, the transmission efficiency and crack resistance may be reduced.

[0128] [additive]

[0129] The rubber composition may contain other fillers (fillers other than carbon black, such as silica, clay, calcium carbonate, talc, mica, etc.), metal powder such as zinc powder, a crosslinking agent (vulcanizing agent), a co-crosslinking agent (vulcanization aid), a crosslinking accelerator (vulcanization accelerator), a crosslinking retarder (vulcanization retarder), a metal oxide (such as zinc oxide, magnesium oxide, lead oxide, calcium oxide, barium oxide, iron oxide, copper oxide, titanium oxide, aluminum oxide, etc.), a softener (oils such as paraffin oil and cycloparaffin oil), a processing agent or a processing aid (fatty acids such as stearic acid, fatty acid metal salts such as stearic acid metal salts, fatty acid amides such as stearic acid amide, wax, paraffin, etc.), an antioxidant (antioxidant, heat aging agent, flex cracking agent, ozone degradation agent, etc.), a colorant, a tackifier, a plasticizer, a lubricant, a coupling agent (silane coupling agent, etc.), a stabilizer (ultraviolet absorber, heat stabilizer, etc.), a flame retardant, an antistatic agent, etc. It should be noted that the metal oxide can function as a cross-linking agent.

[0130] The ratio of the metal powder such as zinc powder is 1 to 100 parts by mass, preferably 3 to 50 parts by mass, more preferably 5 to 30 parts by mass, and even more preferably 8 to 20 parts by mass, relative to 100 parts by mass of the chloroprene rubber.

[0131] As a cross-linking agent, conventional ingredients can be used, and examples thereof include the above-mentioned metal oxides (magnesium oxide, zinc oxide, lead oxide, etc.), organic peroxides (diacyl peroxides, peroxyesters, dialkyl peroxides, etc.), sulfur-based cross-linking agents, etc. As sulfur-based cross-linking agents, for example, powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, sulfur chloride (sulfur monochloride, sulfur dichloride, etc.), etc. can be cited. These cross-linking agents can be used alone or in combination of two or more. Among them, metal oxides (magnesium oxide, zinc oxide, etc.) are preferred. It should be noted that metal oxides can be used in combination with other cross-linking agents (sulfur-based cross-linking agents, etc.), and metal oxides and / or sulfur-based cross-linking agents can be used alone or in combination with cross-linking accelerators.

[0132] The ratio of the cross-linking agent to 100 parts by mass of the chloroprene rubber is, for example, 1 to 20 parts by mass, preferably 3 to 17 parts by mass, more preferably 5 to 15 parts by mass, and further preferably 7 to 13 parts by mass.

[0133] Examples of the co-crosslinking agent (crosslinking aid or co-agent) include known crosslinking aids, such as polyfunctional (iso)cyanurates [e.g., triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), etc.], polydienes (e.g., 1,2-polybutadiene), metal salts of unsaturated carboxylic acids [e.g., polyvalent metal salts of (meth)acrylate such as zinc (meth)acrylate and magnesium (meth)acrylate], oximes (e.g., quinone dioxime), guanidines (e.g., diphenylene glycol), and polyisocyanates. Guanidine, etc.), multifunctional (meth)acrylates [e.g., alkane diol di(meth)acrylates such as ethylene glycol di(meth)acrylate and butanediol di(meth)acrylate, alkane polyol poly(meth)acrylates such as trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate], bismaleimides (aliphatic bismaleimide, such as N,N'-1,2-ethylenebismaleimide, N,N'-hexamethylenebismaleimide, 1,6'-bismaleimide bismaleimide such as bismaleimide-(2,2,4-trimethyl)cyclohexane; bismaleimide or aromatic bismaleimide (such as N,N'-m-phenylene bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 4,4'-diphenylmethane bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 4,4'-diphenyl ether bismaleimide, 4,4'-diphenyl sulfone bismaleimide, 1,3-bis( 3-maleimide phenoxy)benzene, etc.). These crosslinking aids can be used alone or in combination of two or more. Among these crosslinking aids, polyfunctional (iso)cyanurate, polyfunctional (meth)acrylate, bismaleimide (aromatic bismaleimide or aromatic bismaleimide such as N,N'-phenylene bismaleimide), etc., are preferred, and bismaleimide is used in most cases. By adding a crosslinking aid (such as bismaleimide), the degree of crosslinking can be increased, and adhesion wear can be prevented.

[0134] The ratio of the co-crosslinking agent (crosslinking aid) such as bismaleimide is, for example, 0.1 to 20 parts by mass, preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 3 to 8 parts by mass, based on solid content per 100 parts by mass of the chloroprene rubber.

[0135] Examples of the crosslinking accelerator include thiuram-based accelerators [e.g., tetramethylthiuram monosulfide (TMTM), tetramethylthiuram disulfide (TMTD), tetraethylthiuram disulfide (TETD), tetrabutylthiuram disulfide (TBTD), dipentamethylenethiuram tetrasulfide (DPTT), N,N'-dimethyl-N,N'-diphenylthiuram disulfide, etc.], thiazole-based accelerators [e.g., 2-mercaptobenzothiazole, 2-mercaptobenzothiazole], Zinc salt of thiazole, 2-mercaptobenzothiazoline, dibenzothiazole disulfide (MBTS), 2-(4'-morpholinyl dithio)benzothiazole, etc.], sulfonamide accelerators [such as N-cyclohexyl-2-benzothiazole sulfonamide (CBS), N,N'-dicyclohexyl-2-benzothiazole sulfonamide, etc.], guanidines (diphenylguanidine, di-o-tolylguanidine, etc.), urea or thiourea accelerators (such as ethylenethiourea, etc.), dithiocarbamates, xanthates, etc. These crosslinking accelerators can be used alone or in combination of two or more. Among these crosslinking accelerators, TMTD, DPTT, MBTS, CBS, etc. are commonly used.

[0136] The ratio of the crosslinking accelerator is, for example, 0.1 to 10 parts by mass, preferably 0.2 to 5 parts by mass, more preferably 0.3 to 3 parts by mass, further preferably 0.4 to 2 parts by mass, and most preferably 0.5 to 1 part by mass, based on solid content, per 100 parts by mass of the chloroprene rubber.

[0137] The ratio of the softener to 100 parts by mass of the chloroprene rubber is, for example, 1 to 30 parts by mass, preferably 2 to 20 parts by mass, more preferably 3 to 10 parts by mass, and more preferably 4 to 8 parts by mass. In addition, the ratio of the processing agent or processing aid to 100 parts by mass of the chloroprene rubber is, for example, 0 to 10 parts by mass, preferably 0.1 to 5 parts by mass, more preferably 1 to 3 parts by mass, and more preferably 1.5 to 2.5 parts by mass.

[0138] The ratio of the antioxidant is, for example, 0.5 to 15 parts by mass, preferably 1 to 13 parts by mass, more preferably 3 to 12 parts by mass, and further preferably 5 to 10 parts by mass, relative to 100 parts by mass of the chloroprene rubber.

[0139] [Transmission belt]

[0140] The transmission belt of the present invention is not particularly limited as long as it has a compression rubber layer capable of contacting a pulley, and may be a transmission belt having a core layer (adhesive rubber layer), a compression rubber layer formed on one surface of the core layer, and an extension rubber layer formed on the other surface of the core layer. Furthermore, among the transmission belts, a friction transmission belt requiring wear resistance is preferred.

[0141] Examples of friction transmission belts include V-belts [covered V-belts, cut-edge V-belts, cut-edge toothed V-belts (cut-edge toothed V-belts with cogs formed on the inner circumference of cut-edge V-belts, cut-edge double-sided toothed V-belts with cogs formed on both the inner circumference and the outer circumference of cut-edge V-belts)], and poly-V belts. Among these V-belts, V-belts or poly-V belts with a transmission surface inclined in a V shape or at a V angle are preferred. V-belts that are required to have both high levels of wear resistance and fuel economy, such as V-belts used in belt-type continuously variable transmissions (e.g., cut-edge toothed V-belts), are particularly preferred.

[0142] Figure 2 1 is a schematic cross-sectional perspective view showing an example of a transmission belt (a cut-edge toothed V-belt) of the present invention. Figure 3 Yes Figure 2 A schematic cross-sectional view of a transmission belt cut along the length of the belt.

[0143] In this example, the transmission belt 1 has a plurality of cog peaks 1a formed at predetermined intervals along the longitudinal direction of the belt (direction A in the figure) on the inner peripheral surface of the belt body. The cross-sectional shape of the cog peak 1a in the longitudinal direction is formed into an approximately semicircular shape (curved or wavy shape). The cross-sectional shape in the direction orthogonal to the longitudinal direction (width direction or direction B in the figure) is formed into a trapezoidal shape in which the belt width decreases from the outer peripheral side of the belt to the inner peripheral side (cog peak 1a side). That is, the cross-sectional shape of each cog peak 1a in the longitudinal direction (direction A) in the belt thickness direction protrudes from the cog bottom 1b in an approximately semicircular form, and the protruding protrusion with an approximately semicircular cross-sectional shape is continuous along the longitudinal direction (direction A).

[0144] The transmission belt 1 has a laminated structure, and a reinforcing cloth 2, an extended rubber layer 3, a core layer 4, a compression rubber layer 5, and a reinforcing cloth (a reinforcing cloth covering the cog crest 1a and the cog bottom 1b) 6 are laminated in order from the outer peripheral side of the belt to the inner peripheral side (the side where the cog crest 1a is formed). That is, the extended rubber layer 3 and the compression rubber layer 5 are laminated with the core layer 4 interposed therebetween, and the reinforcing cloths 2 and 6 are laminated on the extended rubber layer 3 and the compression rubber layer 5, respectively. Furthermore, a core 4a is buried in the core layer 4, and the above-mentioned cog portion (cog crest 1a and cog bottom 1b) is formed on the compression rubber layer 5 using a molding die with cogs.

[0145] In the transmission belt of the present invention, the compression rubber layer can be formed by the rubber composition (cross-linked rubber composition) of the present invention, and the extended rubber layer, core layer, core and reinforcing cloth are not particularly limited, and can be the extended rubber layer, core layer, core and reinforcing cloth shown below.

[0146] (Extended rubber layer)

[0147] The extension rubber layer may be formed of a rubber composition containing a component selected from the rubber component exemplified in the rubber composition for forming the compression rubber layer, short fibers, an adhesion improver, carbon black, and additives. The extension rubber layer may be a layer formed of the same rubber composition as the compression rubber layer.

[0148] (Core layer)

[0149] The core layer may include a core, and may be a core layer formed only of a core. From the perspective of being able to suppress interlayer peeling and improve belt durability, it is preferably a core layer (adhesive rubber layer) formed of a cross-linked rubber composition in which a core is embedded. The adhesive rubber layer is sandwiched between the extension rubber layer and the compression rubber layer body to bond the extension rubber layer and the compression rubber layer body, and the core may be embedded in the adhesive rubber layer.

[0150] (Adhesive rubber layer)

[0151] Similar to the rubber composition for forming the compression rubber layer, the rubber composition for forming the adhesive rubber layer may contain chloroprene rubber, a crosslinking agent (metal oxides such as magnesium oxide and zinc oxide), a co-crosslinking agent (maleimide-based crosslinking agents such as N,N'-m-phenylene bismaleimide), a crosslinking accelerator (TMTD, DPTT, CBS, etc.), carbon black, a softener (oils such as cycloparaffin oils, aromatic carboxylic acid alkyl esters, etc.), a processing agent or a processing aid (stearic acid, metal stearate, wax, paraffin, etc.), an antioxidant, an adhesion improver (resorcinol resin, amino resin, etc.), a filler (silicon dioxide, clay, calcium carbonate, talc, mica, etc.), a colorant, a tackifier, a plasticizer, a coupling agent (silane coupling agent, etc.), a stabilizer (ultraviolet absorber, heat stabilizer, etc.), a flame retardant, an antistatic agent, etc.

[0152] In the rubber composition, the proportions of the crosslinking agent, co-crosslinking agent, crosslinking accelerator, softener, processing agent or processing aid and antioxidant can be selected from the same ranges as those of the rubber composition for forming the compression rubber layer.

[0153] The ratio of the adhesion improver (second adhesion improver) in the rubber composition for forming the adhesive rubber layer is, for example, 0.5 to 10 parts by mass, preferably 1 to 9 parts by mass, further preferably 2 to 8 parts by mass, more preferably 3 to 7 parts by mass, and most preferably 4 to 6 parts by mass, relative to 100 parts by mass of the chloroprene rubber.

[0154] The ratio of carbon black (second carbon black) in the rubber composition for forming the adhesive rubber layer can be 5 parts by mass or more, for example, 5 to 100 parts by mass, preferably 10 to 100 parts by mass, further preferably 15 to 50 parts by mass, and even more preferably 20 to 40 parts by mass, relative to 100 parts by mass of chloroprene rubber.

[0155] (Core)

[0156] The core body is not particularly limited, and usually core wires (twisted ropes) arranged at prescribed intervals in the belt width direction can be used. The core wires can be arranged extending along the belt length direction, and multiple core wires parallel to the belt length direction are arranged. From the perspective of productivity, the core wires are usually arranged in a spiral shape extending in parallel at prescribed intervals approximately parallel to the belt length direction of the cut-edge toothed V-belt. When the core wires are arranged in a spiral shape, the angle of the core wire relative to the belt length direction can be, for example, 5° or less. From the perspective of belt mobility, the closer to 0°, the more preferred. In addition, the spacing between the core wires is preferably set in the range of 0.5 to 3.0 mm, more preferably in the range of 0.8 to 2.0 mm, and most preferably in the range of 1.0 to 1.6 mm.

[0157] The core wire may be embedded in the adhesive rubber layer, embedded between the adhesive rubber layer and the extension rubber layer, or embedded between the adhesive rubber layer and the compression rubber layer. Among them, the core wire is preferably embedded in the adhesive rubber layer from the aspect of improving durability.

[0158] As the fiber constituting the core yarn, the same fibers as those mentioned above can be exemplified. Among the above fibers, C esters such as ethylene terephthalate and ethylene 2,6-naphthalate are commonly used from the perspective of high modulus. 2-4 Alkylene-C 8-12 Polyester fibers (polyalkylene arylate fibers), synthetic fibers such as aramid fibers, inorganic fibers such as carbon fibers, etc., with arylate as the main structural unit, preferably polyester fibers (polyethylene terephthalate fibers, polyethylene naphthalate fibers) and aramid fibers. These fibers can be used in the form of a multifilament yarn containing a plurality of filaments. The fineness of the multifilament yarn is, for example, 200 to 5000 dtex (particularly 500 to 2000 dtex). The multifilament yarn contains, for example, 100 to 5000 filaments, preferably 500 to 4000 filaments, and more preferably 1000 to 3000 filaments. When the core thread is composed of polyester fibers, the multifilament yarn contains, for example, 50 to 1500 filaments, preferably 100 to 1000 filaments, and more preferably 300 to 500 filaments.

[0159] As the core wire, a twisted rope (such as ply twist, unidirectional twist, straight twist, etc.) using a multifilament yarn can generally be used. The total fineness of the core wire (twisted rope) is, for example, 3000 to 30000 dtex, preferably 4000 to 15000 dtex, and more preferably 5000 to 8000 dtex. The core wire (twisted rope) can contain, for example, 1000 to 15000 filaments, preferably 2000 to 10000 filaments, and more preferably 5000 to 7000 filaments. When the core wire is composed of polyester fiber, the core wire can contain, for example, 500 to 12000 filaments, preferably 1000 to 5000 filaments, and more preferably 2000 to 3000 filaments. The average wire diameter of the core wire (diameter of the twisted rope) can be, for example, 0.5 to 3 mm, preferably 0.6 to 2 mm, and more preferably 0.7 to 1.5 mm.

[0160] In order to improve the adhesion with chloroprene rubber, the core wire can be subjected to an adhesive treatment or surface treatment in the same manner as the short fibers. The core wire is also preferably subjected to an adhesive treatment with at least an RFL liquid in the same manner as the short fibers.

[0161] (Reinforced cloth)

[0162] A reinforcing cloth may be laminated on the surface of the compression rubber layer and / or the extension rubber layer. The reinforcing cloth may be formed, for example, by laminating a woven cloth, a wide canvas, a knitted cloth, a nonwoven cloth or the like (preferably a woven cloth) on the surface of the compression rubber layer and / or the extension rubber layer. The reinforcing cloth may be subjected to the above-mentioned bonding treatment as required, for example, treatment with an RFL liquid (immersion treatment, etc.), or friction treatment in which the adhesive rubber is rubbed into the above-mentioned cloth material, and after laminating the above-mentioned adhesive rubber with the above-mentioned cloth material, it may be laminated on the surface of the compression rubber layer and / or the extension rubber layer.

[0163] (Manufacturing method of transmission belt)

[0164] The method for producing the power transmission belt (eg, cut-edge toothed V-belt) of the present invention is not particularly limited, and the lamination step of each layer (the method for producing the belt sleeve) can be performed by a conventional method according to the type of belt.

[0165] For example, a typical method for manufacturing a cut edge toothed V-belt is described below. First, a laminate of a reinforcing cloth (lower cloth) and a compression rubber layer sheet (uncrosslinked rubber sheet) is alternately arranged with the reinforcing cloth on the lower side and the cogs ( Figure 2The toothed ridge 1a and the toothed bottom 1b shown in the figure are placed in contact with the flat cog-shaped forming die of the toothed portion and the groove portion. Then, pressing and pressurizing are performed at a temperature of about 60°C to about 100°C (especially about 70°C to about 80°C), thereby manufacturing a toothed gasket (a gasket that is not completely cross-linked and is in a semi-cross-linked state) molded with a cog portion. Then, both ends of the toothed gasket are vertically cut from appropriate positions (especially the top of the cog ridge) to obtain the required length.

[0166] Next, an inner mother mold having teeth and grooves corresponding to the above-mentioned cogging parts alternately arranged is applied to the outer periphery of the cylindrical mold, and the teeth of the inner mother mold are engaged with the grooves, and then a toothed gasket is wound around the two ends (especially the top of the cogging mountain part) to join. Then, after the first adhesive rubber layer sheet (lower adhesive rubber: uncrosslinked rubber sheet) is laminated on the outer periphery of the toothed gasket, the core wire (twisted rope) forming the core body is spirally wound. Then, the second adhesive rubber layer sheet (upper adhesive rubber: uncrosslinked rubber sheet), the stretching rubber layer sheet (uncrosslinked rubber sheet), and the upper cloth are sequentially wound around the outer periphery to produce an uncrosslinked molded body.

[0167] Then, the uncrosslinked molded body is placed in a known crosslinking device (vulcanizing tank, etc.) in a state where the sheath is coated on the uncrosslinked molded body, and crosslinked and molded at a temperature of 120 to 200°C (particularly 150 to 180°C) to produce a crosslinked belt sleeve. Then, the crosslinked belt is cut into a V shape using a cutter, etc., to obtain an annular cut-edge toothed V belt.

[0168] The method for manufacturing a transmission belt of the present invention includes a kneading step of kneading the rubber composition of the present invention to manufacture an uncrosslinked rubber sheet for forming a compression rubber layer. Although the rubber composition contains an adhesion improver, the rubber composition does not adhere to a mixer during the kneading step, and the uncrosslinked rubber sheet can be manufactured smoothly.

[0169] Example

[0170] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. It should be noted that the following shows the details of the materials used in the examples, the method for preparing the uncrosslinked rubber sheet, and the methods for measuring or evaluating the various physical properties.

[0171] [Materials used]

[0172] (Rubber component)

[0173] Neoprene: "PM-40" manufactured by Denka Corporation

[0174] (Short Fiber)

[0175] The following short fibers were used for the short fibers. All the short fibers were subjected to a bonding treatment by being immersed in an RFL liquid [a mixed solution of 2.6 parts by mass of resorcinol, 1.4 parts by mass of 37% formalin, 17.2 parts by mass of vinyl pyridine-styrene-butadiene copolymer latex (manufactured by Japan Zeon Co., Ltd.), and 78.8 parts by mass of water] and dried. The adhesion rate of the bonding component (solid content) was adjusted to 6% by mass relative to the short fibers.

[0176] Meta-aramid staple fiber: "Conex" manufactured by Teijin Limited, fiber length 3 mm

[0177] Para-aramid staple fiber A: "Towaron (registered trademark)" manufactured by Teijin Limited, fiber length 3 mm

[0178] Para-aramid staple fiber B: "Towaron (registered trademark)" manufactured by Teijin Limited, fiber length 1 mm

[0179] Nylon 66 staple fiber A: "Leona" manufactured by Asahi Kasei Corporation, fiber length 3 mm

[0180] Nylon 66 staple fiber B: "Leona" manufactured by Asahi Kasei Corporation, fiber length 1 mm

[0181] (filler)

[0182] Carbon black FEF: "Shutter SO" manufactured by Tokai Carbon Co., Ltd.

[0183] Carbon black ISAF: "Size 6" manufactured by Tokai Carbon Co., Ltd.

[0184] Silica: "Nipsil VN3" manufactured by Tosoh Silica Chemicals Co., Ltd.

[0185] (additive)

[0186] Zinc powder: "M-11" manufactured by Sakai Chemical Industry Co., Ltd.

[0187] Naphthenic oil: "Naphthenic oil NS-90S" manufactured by Idemitsu Kosan Co., Ltd.

[0188] Adhesion improver A (resorcinol-formaldehyde co-condensate): "POWERPLAST PP-1860" manufactured by Singh Plasticisers & Resins

[0189] Adhesion improver B (hexamethoxymethyl melamine): "POWERPLAST PP-1890S" manufactured by Singh Plasticisers & Resins

[0190] Adhesion improver C (cresol-formaldehyde co-condensate): "Sumikanoul 610" manufactured by Taoka Chemical Industry Co., Ltd.

[0191] Adhesion improver D (novolak resin): "Sumilyte Resin PR-12687" manufactured by Sumitomo Bakelite Co., Ltd.

[0192] Magnesium oxide: Kyowa Chemical Industry Co., Ltd. "Kiowa Mag 150"

[0193] Crosslinking accelerator MBTS (dibenzothiazole disulfide): "Noxelara DM" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0194] Crosslinking accelerator TMTD (tetramethylthiuram disulfide): "Nokusela TT" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0195] Anti-aging agent A (octyldiphenylamine): "NonFlorex OD-3" manufactured by Seiko Chemical Co., Ltd.

[0196] Antiaging agent B (4,4'-bis(α,α-dimethylbenzyl)diphenylamine): "Nonflex DCD" manufactured by Seiko Chemical Co., Ltd.

[0197] Anti-aging agent C (microcrystalline wax): "Santai C" manufactured by Seiko Chemical Co., Ltd.

[0198] Softener: ADK CIZER C-8 manufactured by ADEKA Corporation

[0199] Stearic acid: "Stearic acid つばき" manufactured by NOF Co., Ltd.

[0200] Zinc oxide: "Zinc oxide (JIS standard 2 type)" manufactured by Hakusui Tech Co., Ltd.

[0201] Co-crosslinking agent (N,N'-m-phenylene bismaleimide): "Varnouck PM" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0202] (core wire)

[0203] A pre-twisted yarn was obtained by combining two 1100 dtex PET fiber bundles and pre-twisting them at a twist coefficient of 3.0. A ply-twisted rope with a total fineness of 6600 dtex was obtained by combining three of the pre-twisted yarns and final twisting them at a twist coefficient of 3.0 as a core yarn. The core yarn was subjected to the same bonding treatment as the staple fibers.

[0204] (Reinforced cloth)

[0205] A canvas (weight per unit area 180 g / m2) was obtained by flat-weaving 10-count cotton yarn at a yarn density of 70 yarns / 50 mm. 2 A treated canvas (thickness of about 0.5 mm, weight per unit area of ​​about 450 g / m2) was used in which the rubber composition for the adhesive rubber layer was rubbed into the canvas. 2 ) as a reinforcing cloth. The same reinforcing cloth is used for both the inner and outer sides of the belt.

[0206] [Whether there is sticking during the kneading process]

[0207] The rubber composition was evaluated for sticking to the mixer when it was kneaded in a closed mixer (Banbury mixer). If the rubber composition was automatically discharged from the mixer, it was judged to be non-sticky (good), and if the rubber composition stuck to the mixer needed to be peeled off with a tape hook, it was judged to be sticky (problematic).

[0208] [Friction coefficient]

[0209] The rubber composition was pressed and heated at a temperature of 160°C and a pressure of 0.9 MPa for 20 minutes to produce a cross-linked rubber sheet with a thickness of 2 mm. A disc-shaped test piece with a diameter of 8 mm and a thickness of 2 mm was cut from the cross-linked rubber sheet, and the friction force was measured using a pin-on-disk friction coefficient measuring device to calculate the friction coefficient. Specifically, the target material (SUS304) with a surface roughness Ra of 0.8 μm was used at 2.192 kgf / cm 2 The test piece was pressed with a load of 1.50 and the friction force was measured at a friction speed of 0 to 2.0 m / sec. In Tables 3 to 5, the relative values ​​are shown when the friction coefficient of Comparative Example 1 is set to 100. The smaller the value, the more the wear resistance and fuel saving of the transmission belt tend to be improved.

[0210] [8% bending stress (orthogonal to short fibers)]

[0211] The uncrosslinked rubber composition having the composition shown in Tables 3 to 5 was pressed and heated at a temperature of 160°C and a pressure of 0.9 MPa for 20 minutes to produce a crosslinked rubber molded body (60 mm × 25 mm × 6.5 mm in thickness). The short fibers were oriented parallel to the length direction of the crosslinked rubber molded body. Figure 4As shown, the cross-linked rubber molded body 21 is supported by placing a pair of rotatable rollers (diameter 6 mm) 22a and 22b at a distance of 20 mm, and a metal pressing member 23 is placed in the width direction (direction orthogonal to the orientation direction of the short fibers) at the center of the upper surface of the cross-linked rubber molded body. The front end of the pressing member 23 has a semicircular shape with a diameter of 10 mm, and the cross-linked rubber molded body 21 can be pressed smoothly by the front end. In addition, when pressing, friction acts between the lower surface of the cross-linked rubber molded body 21 and the rollers 22a and 22b with the compression deformation of the cross-linked rubber molded body 21, but the influence of friction is reduced by making the rollers 22a and 22b rotatable. The front end of the pressing member 23 contacts the upper surface of the cross-linked rubber molded body 21, and the state of not pressing is set as the initial position. From this state, the pressing member 23 presses the upper surface of the cross-linked rubber molded body 21 downward at a speed of 100 mm / min, and the stress when the bending strain is 8% is measured as the bending stress. The measurement temperature is assumed to be the belt temperature during running, and is set to 120°C. The greater the 8% bending stress in the orthogonal direction of the short fibers, the higher the resistance to buckling deformation (concave bending) during running of the belt, and the better the wear resistance and fuel saving performance. 6.3MPa or more is judged as a qualified level for practical use.

[0212] [Bending fatigue resistance (Demesia bending test)]

[0213] The measuring method is in accordance with JIS K6260:2017 (Vulcanized rubber and thermoplastic rubber-Method for determining resistance to bending cracking and resistance to bending crack growth (Demessia type)). The rubber composition is cross-linked using a mold to produce a test piece (cross-linked rubber molded body) having a length of 140 mm, a width of 25 mm, a thickness of 6.3 mm, and a semicircular depression with a radius of curvature of 2.38 mm in the central part of the length direction. It should be noted that the short fibers are oriented in a manner parallel to the length direction of the test piece. The test method adopts a test for measuring the number of bends required until a crack of a specified length is generated when the test piece is repeatedly bent and deformed without introducing an incision, i.e., a bending crack generation test. The maximum distance between the clamps of the Demessia type bending tester is 75 mm, the reciprocating motion distance (stroke) is set to 57 mm, the reciprocating motion speed is set to 300 times per minute, and the measuring temperature (atmospheric temperature) is set to 120°C. When the number of bends reaches the specified number, the distance between the clamps is 65 mm, and the test machine is temporarily stopped to confirm the presence or absence of cracks and the length of the cracks (the length in the width direction of the test piece). The test is terminated when the length of the crack reaches 3 mm. In Tables 3 to 5, the relative values ​​are expressed when the number of bends when the crack length of Comparative Example 1 reaches 3 mm is set to 100. The larger the value, the better the bending fatigue resistance (cracking resistance).

[0214] [Transmission efficiency (power transmission efficiency)]

[0215] like Figure 5 As shown, the transmission efficiency test is carried out using a double-axis running tester including a drive (Dr.) pulley with a diameter of φ95mm connected to the drive shaft and a driven (Dn.) pulley with a diameter of φ110mm connected to the driven shaft. The drive shaft and the driven shaft are connected to the motor, and a torque meter and a digital tachometer are installed to adjust the speed and torque. A trimmed toothed V-belt is wound on each pulley, and a tension is applied to the belt with an axial load of 300N. The speed of the drive pulley is adjusted to about 3,000rpm and the torque is 2Nm, and the torque and speed of the drive shaft and the driven shaft at this time are measured. The measurement temperature (atmospheric temperature) is set to 25°C.

[0216] As shown in the following formula, the power P of the drive shaft 1 The torque T of the drive shaft 1 and speed ρ 1 Similarly, the power P of the driven shaft is 2 The torque T of the driven shaft 2 and speed ρ 2 The transmission efficiency η is obtained by dividing the power of the driven shaft by the power of the driving shaft.

[0217] P 1 =T 1 ×ρ 1

[0218] P 2 =T 2 ×ρ 2

[0219] η=P 2 / P 1 =(T 2 ×ρ 2 ) / (T 1 ×ρ 1 )

[0220] It should be noted that if there is no transmission loss, the transmission efficiency value is 1. If there is transmission loss, the transmission efficiency value is reduced by the value of the loss. That is, the closer the transmission efficiency value is to 1, the smaller the transmission loss of the belt is, and the better the fuel saving performance is.

[0221] In Tables 3 to 5, relative values ​​are shown when the transmission efficiency of Comparative Example 1 is set to 100. When the value is 90 or more, it is judged that the fuel saving performance is excellent (a pass level for practical use).

[0222] [Wear durability test (upper width change)]

[0223] like Figure 6As shown in the figure, the wear durability test was conducted using a double-axis running test machine including a driving (Dr.) pulley with a diameter of 60 mm and a driven (Dn.) pulley with a diameter of 145 mm. A trimmed toothed V-belt was wound around the two pulleys, the shaft load was set to 1000 N, the rotation speed of the driving pulley was set to 6500 rpm, and the load on the driven pulley was set to 15 N·m, and the belt was run for 20 hours at an ambient temperature of 60°C. The upper width of the belt was measured before and after running, and when the change in the upper width (wear loss) was less than 0.4 mm, it was judged to be excellent in wear resistance (a qualified level for practical use).

[0224] [Crack durability test (crack depth)]

[0225] like Figure 7 As shown in the figure, the crack durability test is conducted using a double-axis running test machine including a driving (Dr.) pulley with a diameter of 115 mm and a driven (Dn.) pulley with a diameter of 95 mm. A cut-edge toothed V-belt is wound around the two pulleys, the axial load is set to 500 N, the rotation speed of the driving pulley is set to 9000 rpm, and the load on the driven pulley is set to 10 N·m, and the belt is run for 96 hours at an ambient temperature of 100°C. The depth of the cracks generated in the cog valleys of the belt after running (the length in the belt thickness direction) is measured. When the depth of the cracks is less than 3 mm, it is judged that the crack resistance is excellent (a qualified level for practical use).

[0226] Examples 1 to 20 and Comparative Examples 1 to 10

[0227] (Formation of rubber layer)

[0228] The rubber compositions of Table 2 (adhesive rubber layer) and Tables 3 to 5 (compression rubber layer and stretching rubber layer) were respectively kneaded using a known method such as a Banbury mixer, and the resulting kneaded rubber was passed through a calendering roller to produce a calendered rubber sheet (sheet for the adhesive rubber layer, sheet for the compression rubber layer, sheet for the stretching rubber layer).

[0229] (Manufacture of belt)

[0230] The laminate of the reinforcing cloth (lower cloth) and the compressed rubber layer sheet (uncrosslinked rubber) is placed on a flat cog-toothed mold with teeth and grooves corresponding to the cogs alternately arranged in such a way that the reinforcing cloth is placed at the bottom. The laminate is pressed at 75°C to produce a toothed gasket (not completely crosslinked, in a semi-crosslinked state) molded with a cog. Next, the two ends of the toothed gasket are cut vertically from the top of the cog mountain.

[0231] Next, an inner mother mold having teeth and grooves corresponding to the above-mentioned cogging parts arranged alternately is placed on a cylindrical mold, and the teeth of the inner mother mold are engaged with the grooves, and then the toothed gasket is wound to join the top of the cogging mountain part. After the first adhesive rubber layer sheet (lower adhesive rubber, uncrosslinked rubber, the same as the above-mentioned adhesive rubber layer sheet) is laminated on the outer periphery of the wound toothed gasket, a core wire is spirally wound (core wire pitch 1.1 mm), and the second adhesive rubber layer sheet (upper adhesive rubber, the same as the above-mentioned adhesive rubber layer sheet), the stretching rubber layer sheet (uncrosslinked rubber), and the upper cloth are sequentially wound on the outer periphery to produce an uncrosslinked molded body.

[0232] Then, after the uncrosslinked molded body is covered with a sheath, the mold is placed in a vulcanizer and crosslinked at a temperature of 160°C for 20 minutes to obtain a belt sleeve. The belt sleeve is cut into a V-shaped cross-sectional shape with a predetermined width in the belt length direction using a cutter. Then, the belt sleeve is finished into Figure 2 The belt of the structure shown is a cut-edge toothed V-belt (dimensions: upper width 23.5 mm, thickness 11.0 mm, outer circumference 850 mm) as a speed change belt having cogs on the inner circumference of the belt.

[0233] Tables 3 to 5 show the evaluation results of the tapes obtained in Examples and Comparative Examples.

[0234] [Table 2]

[0235]

[0236] [Table 3]

[0237]

[0238] [Table 4]

[0239]

[0240] [Table 5]

[0241]

[0242] Comparative Examples 1 and 5 are examples in which no adhesion improver was included, and the crack resistance was low. In Comparative Example 2, the amount of adhesion improver was too large, so sticking occurred during the kneading step.

[0243] Comparative Example 3 is an example in which the amount of para-aramid short fibers is large, and the friction coefficient is large, so the power transmission efficiency is low and the crack resistance is also low.

[0244] Comparative Example 4 is an example in which the total amount of short fibers is large, and the crack resistance is low. Comparative Example 6 is an example in which the total amount of short fibers is small, and the bending stress is small, and the wear resistance is low.

[0245] Comparative Example 7 is an example in which the amount of carbon black is too much, and the transmission efficiency and crack resistance are low. Comparative Example 8 is an example in which the amount of carbon black is too little, and the bending stress and wear resistance are low. Comparative Example 9 is an example in which the amount of adhesion improver is too little, and the crack resistance is low. Comparative Example 10 is an example in which aramid short fibers are not contained, and the bending stress is small and the wear resistance is low.

[0246] When Examples 1 to 3 are compared, it can be confirmed that the crack resistance is improved when the amount of the adhesion improver is large.

[0247] By comparing Example 1 with Example 4, it can be confirmed that if hard carbon (ISAF) is used, the transmission efficiency becomes low, and therefore soft carbon (FEF) is preferable.

[0248] By comparing Example 1 with Example 5, it can be confirmed that as the amount of the aramid short fibers increases, the friction coefficient increases, and the power transmission efficiency and crack resistance decrease.

[0249] In Example 6, the amount of nylon short fibers was larger than the amount of aramid short fibers. It was confirmed that the power transmission efficiency was increased, but the crack resistance was decreased.

[0250] In Example 8, in which the short fibers were made of only para-aramid short fibers, the friction coefficient was higher and the transmission efficiency was lowered compared to Example 7, in which the short fibers were made of only meta-aramid short fibers. It can be said that when the short fibers were made of only aramid short fibers, it is preferable to use meta-aramid short fibers.

[0251] By comparing Example 1 with Example 10, when nylon staple fibers and aromatic polyamide staple fibers are used in combination, when meta-aramid staple fibers are used, the result is a greater effect of improving the transmission efficiency, and when para-aramid staple fibers are used, the result is excellent bending fatigue resistance and crack resistance.

[0252] Example 9 is an example in which the fiber length of the nylon staple fibers is as short as 1 mm. Compared with Example 1 in which the fiber length of the nylon staple fibers is 3 mm, the bending fatigue resistance and the crack resistance are lowered.

[0253] By comparing Example 1 with Example 11, it can be confirmed that when the amount of carbon black is reduced, the transmission efficiency and crack resistance are improved, and the bending stress and wear resistance are reduced.

[0254] By comparing Example 1 with Example 12, it can be confirmed that when the amount of carbon black increases, the bending stress and wear resistance increase, and the bending fatigue resistance, transmission efficiency, and crack resistance decrease.

[0255] Examples 13 to 15 are examples in which the type of the adhesion improver was changed, and all of them had the same results as Example 1.

[0256] Example 16 is an example in which the fiber length of the para-aramid short fibers is as short as 1 mm. Compared with Example 1 in which the fiber length of the para-aramid short fibers is 3 mm, the bending fatigue resistance and the crack resistance are lowered.

[0257] In Example 17, the amount of aramid short fibers was reduced and the amount of nylon short fibers was increased. It was confirmed that the power transmission efficiency was improved, but the crack resistance was reduced.

[0258] By comparing Example 1, Example 6, and Examples 17 to 20, it can be confirmed that if the ratio of the amount of nylon staple fibers to the amount of aramid staple fibers increases, the transmission efficiency increases, while on the other hand, the wear resistance and crack resistance decrease. It can also be confirmed that if the ratio of the amount of nylon staple fibers to the amount of aramid staple fibers decreases, the bending stress increases, the wear resistance increases, and on the other hand, the transmission efficiency and crack resistance decrease. It is believed that Example 1, which maintains high transmission efficiency and wear resistance and has the highest crack resistance among these examples, is the best mode.

[0259] The present invention is described in detail and with reference to specific embodiments, but it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on Japanese patent applications (Japanese patent applications 2022-104906) filed on June 29, 2022, Japanese patent applications (2023-016797) filed on February 7, 2023, and Japanese patent applications (2023-088786) filed on May 30, 2023, and the contents are incorporated herein by reference.

[0260] Industrial Applicability

[0261] The rubber composition of the present invention can be used for various molded bodies, and can be used as a transmission belt, for example, a friction transmission belt such as a flat belt, a wrapped V-belt, a trimmed V-belt, a trimmed toothed V-belt, a multi-ribbed belt, and a meshing transmission belt such as a toothed belt and a double-sided toothed belt. In particular, if the rubber composition of the present invention is used as a compression rubber layer of a transmission belt, wear resistance, fuel saving, and crack resistance can be improved at the same time. Therefore, the rubber composition of the present invention is useful for the compression rubber layer of a speed change belt used in a motorized two-wheeled motorcycle, a four-wheeled all-terrain vehicle, a snowmobile, an agricultural machine, etc., which are being promoted to increase horsepower.

[0262] Explanation of symbols

[0263] 1…Drive belt

[0264] 2, 6…Reinforced fabric

[0265] 3…Extended rubber layer

[0266] 4…Core layer

[0267] 4a…Core

[0268] 5…Compression rubber layer

Claims

1. A rubber composition, which is a rubber composition for a compression rubber layer of a transmission belt, wherein: The rubber composition comprises chloroprene rubber, short fibers, an adhesion improver and carbon black. The staple fibers include aramid staple fibers, With respect to 100 parts by mass of the chloroprene rubber, the ratio of the short fibers is 15 to 38 parts by mass, the ratio of the aramid short fibers is 5 to 28 parts by mass, the ratio of the adhesion improver is 0.1 to 3.2 parts by mass, and the ratio of the carbon black is 30 to 70 parts by mass.

2. The rubber composition according to claim 1, wherein The short fibers also include aliphatic polyamide short fibers, The ratio of the aliphatic polyamide short fibers is 25 parts by mass or less relative to 100 parts by mass of the chloroprene rubber.

3. The rubber composition according to claim 2, wherein The aliphatic polyamide staple fibers have an average fiber length of 1.5 mm or more.

4. The rubber composition according to any one of claims 1 to 3, wherein The carbon black includes soft carbon.

5. The rubber composition according to any one of claims 1 to 4, wherein The adhesion improver includes a phenolic resin and / or an amino resin. 6 . A transmission belt comprising a compression rubber layer, wherein the compression rubber layer comprises the rubber composition according to claim 1 . 7 . A method for producing a transmission belt, comprising a kneading step of kneading the rubber composition according to claim 1 to produce an uncrosslinked rubber sheet for forming a compression rubber layer.

Citation Information

Patent Citations

  • Transmission belt

    JP1992366045A

  • Transmission belt

    JP2004003609A

  • Transmission belt

    JP2010151209A

  • Power transmission belt

    JP2012241831A

  • Transmission belt

    JP2014209026A